Role of Chest Imaging in Clinically Suspected Extrapulmonary Tuberculosis Without any Chest Symptoms - Sumit Kumar; Aishwarya Naik; Vinita Rathi; Anupama Tandon (National Journal of Medical Research)
Background: Establishing a definitive diagnosis of EPTB can be very difficult in resource limited developing countries. Objective: To assess whether chest imaging (chest radiograph and/or CT chest) can play a significant role in the diagnosis of suspected EPTB.